'Children not trophies': An ethnographic study of private family law practice in England. (September 2020) - Holt, Kim; Kelly, Nancy
The welfare of the child in the context of private family law proceedings is of significant international interest. This paper presents findings from an ethnographic study of private law proceedings in England, which explored legal professionals' experiences of and practice within space and place. Data are derived from interviews with professionals, and observations from the waiting areas, canteens, interview rooms and offices of lawyers who represent parents in private family law proceedings. The paper focuses on winners and losers in the area of private family law, and the 'trophy', the child, who appears to be lost in the battleground of legal proceedings, but remains the ultimate prize. The concept of space is explored before moving to reflect upon the data from the interviews. The themes that emerge from the data are the relationships between the public space of the court and the vulnerability of the parties as they attempt with greater or less ease, to navigate the complexities of this formal and procedurally driven space. This paper explores the idea of the child as the ultimate 'trophy' within private law proceedings to consider its significance for family justice practice in England, and to elicit a greater understanding of the importance of space and place in private law proceedings that have remained largely unexplored.